2021
DOI: 10.1002/est2.273
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on effects of axially and radially cascaded phase change material on charging/discharging time of paraffin based packed bed thermal energy storage

Abstract: This study manifests the improvement in the charging and discharging time of the encapsulated PCM arranged in packed bed thermal energy storage. The combined effect of the aspect ratio (ratio of height to diameter of the packed bed) and cascaded configurations of phase change materials (PCMs) integrated with the solar water heating system is analyzed numerically. The mathematical model is validated by the experimental study available in the literature. Initially, an optimal aspect ratio of the packed bed is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This approach offers several advantageous features, including minimal temperature variation during the storage process and high storage capacity. Over the past three decades, numerous studies have focused on exploring the benefits of LTES, [1][2][3][4][5] comparing various LTES configurations, 6,7 developing novel classes of PCMs, 8,9 and implementing LTES in solar domestic hot water (SDHW) systems. [10][11][12][13] Due to the low thermal conductivity of most PCMs, the heat transfer rate within LTES systems is limited, resulting in a reduced phase change rate during charging and discharging periods.…”
Section: Introductionmentioning
confidence: 99%
“…This approach offers several advantageous features, including minimal temperature variation during the storage process and high storage capacity. Over the past three decades, numerous studies have focused on exploring the benefits of LTES, [1][2][3][4][5] comparing various LTES configurations, 6,7 developing novel classes of PCMs, 8,9 and implementing LTES in solar domestic hot water (SDHW) systems. [10][11][12][13] Due to the low thermal conductivity of most PCMs, the heat transfer rate within LTES systems is limited, resulting in a reduced phase change rate during charging and discharging periods.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, (Rabbi, Asif, and Bibi 2021) studied the aspect ratio of packed bed type thermal energy storage and results indicated that by increasing aspect ratio charging time was decreased.…”
Section: Introductionmentioning
confidence: 99%